2018
DOI: 10.1159/000489600
|View full text |Cite
|
Sign up to set email alerts
|

Language Exposure of Preterm Infants in the Neonatal Unit: A Systematic Review

Abstract: Background: Elevated sound levels and low language exposures of preterm infants (< 37 weeks) cared for in the neonatal unit contribute to poorer growth, cognition, language and motor outcomes. These delays can have lasting effects on childhood development and continue throughout adult life. Whilst recommendations have been established for appropriate sound exposure levels in neonatal units, very little is known about the optimal level of language exposure. Objectives: To examine the evidence regarding language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
1
39
1
Order By: Relevance
“…Bayley Scales of Infant Toddler Development) lends additional credence to our findings with regard to low language difficulty rates and risk factors affecting language outcomes in this group. The language difficulties shown here, poorly predicted by medical factors, may support emerging arguments that the linguistic environment of the neonatal intensive care unit is a powerful contributor to later language performance . However, further research will be required to determine the contribution of linguistic deprivation in the neonatal period versus other possible predictors such as parent–child interaction style and exposure to early learning environments.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Bayley Scales of Infant Toddler Development) lends additional credence to our findings with regard to low language difficulty rates and risk factors affecting language outcomes in this group. The language difficulties shown here, poorly predicted by medical factors, may support emerging arguments that the linguistic environment of the neonatal intensive care unit is a powerful contributor to later language performance . However, further research will be required to determine the contribution of linguistic deprivation in the neonatal period versus other possible predictors such as parent–child interaction style and exposure to early learning environments.…”
Section: Discussionsupporting
confidence: 52%
“…The language difficulties shown here, poorly predicted by medical factors, may support emerging arguments that the linguistic environment of the neonatal intensive care unit is a powerful contributor to later language performance. 23 However, further research will be required to determine the contribution of linguistic deprivation in the neonatal period versus other possible predictors such as parent-child interaction style and exposure to early learning environments. Our findings indicate that children born preterm vary substantially in their communication profiles.…”
Section: Discussionmentioning
confidence: 99%
“…due to preterm birth) are widely known to experience adverse neurodevelopmental outcomes . Researchers have suggested that some of these neurodevelopmental outcomes might be attributed to the sensory and linguistic deprivation that characterises time spent in hospital, rather than to the medical conditions and interventions that necessitate hospitalisation . Thus, there is an increasing interest in non‐invasive environmental enrichment therapies in the neonatal intensive care unit (NICU), including music therapy .…”
mentioning
confidence: 99%
“…In this systematic review, Best, Bogossian, and New examined observational and intervention studies of language exposure for hospitalised preterm neonates. Ten studies met their inclusion criteria.…”
mentioning
confidence: 99%
“…Adequately powered, randomized controlled trials using appropriate stimuli will be critical, and, as the authors suggest, longer term follow‐up is indicated. The authors suggest ‘2 years’ corrected age and beyond’ as a target for longitudinal studies of intervention outcomes. We emphasise ‘and beyond’, given that language development is notoriously unstable at two years’, and longer term follow‐up may be necessary to obtain valid outcomes .…”
mentioning
confidence: 99%